Activation of NOTCH signaling via DLL1 is mediated by APE1-redox-dependent NF-κB activation in oesophageal adenocarcinoma. Issue 3 (24th June 2022) - Chen, Lei; Lu, Heng; Peng, Dunfa; Cao, Long Long; Ballout, Farah; Srirmajayam, Kannappan; Chen, Zheng; Bhat, Ajaz; Wang, Timothy C; Capobianco, Anthony; Que, Jianwen; McDonald, Oliver Gene; et al.
Abstract : Objective: Oesophageal adenocarcinoma (EAC) arises in the setting of Barrett's oesophagus, an intestinal metaplastic precursor lesion that can develop in patients with chronic GERD. Here, we investigated the role of acidic bile salts, the mimicry of reflux, in activation of NOTCH signaling in EAC. Design: This study used public databases, EAC cell line models, L2-IL1β transgenic mouse model and human EAC tissue samples to identify mechanisms of NOTCH activation under reflux conditions. Results: Analysis of public databases demonstrated significant upregulation of NOTCH signaling components in EAC. In vitro studies demonstrated nuclear accumulation of active NOTCH1 cleaved fragment (NOTCH intracellular domain) and upregulation of NOTCH targets in EAC cells in response to reflux conditions. Additional investigations identified DLL1 as the predominant ligand contributing to NOTCH1 activation under reflux conditions. We discovered a novel crosstalk between APE1 redox function, reflux-induced inflammation and DLL1 upregulation where NF-κB can directly bind to and induce the expression of DLL1. The APE1 redox function was crucial for activation of the APE1-NF-κB-NOTCH axis and promoting cancer cell stem-like properties in response to reflux conditions. Overexpression of APE1 and DLL1 was detected in gastro-oesophageal junctions of the L2-IL1ß transgenic mouse model and human EAC tissue microarrays. DLL1 high levels were associated with poor overall survival in patients with EAC. Conclusion: These findings underscore a unique mechanism that links redox balance, inflammation and embryonic development (NOTCH) into a common pro-tumorigenic pathway that is intrinsic to EAC cells.